Liên hệ giữa nguyên lý entropy cực đại và giả thiết độc lập có điều kiện trong logic xác suất - Tùng, Hà Đặng Cao (Journal of Computer Science and Cybernetics, 2016)
In the Probabilistic Logic, the single value of the truth probability of a sentence is calculated by adding some assumptions. By adding the Maximum Entropy Principle (MEP) the reasoning problem becomes a nonlinear optimization problem. In this note we assert the equivalence between the MEP and the Conditional Independence Assumption (CIA) and Randomness Assumption (RA) formulas for a class of Probabilistic Knowledge Base. Then instead of solving a nonlinear optimization problem to find the truth probability of a sentence, we can derive it from Calculua C and some CIA + RA formulas.